(untitled) (Papeles, 2022)
Introduction: The present study has two general objectives: on the one hand, to analyse how Academic Engagement and Grit vary in students of a postgraduate course taught in face-to-face and online modality at Universidad Austral (Argentina); and to analyse how the values achieved by students in both constructs are related to their level of academic achievement. Methodology: For this purpose, a quantitative, cross-sectional, descriptive and correlational design was implemented, in which a non-probabilistic and convenience sample was formed. The sample was made up of 121 students of the referred postgraduate course, which is aimed at training managers of educational institutions; who completed a sociodemographic questionnaire, the UWES-SS Scale and the Grit-O Scale; and to evaluate achievement, the final grades obtained by the students in specific subjects of the study syllabus were considered. Results and discussion: Based on the hypotheses proposed, no significant differences were found according to sex; significant and positive correlations were found between some of the subscales that make up the instruments; additionally, it was found that students in the degree program taught online obtained higher values in the variables absorption and global commitment of the UWES-SS Scale; finally, it was found that academic achievement is not directly affected by the teaching modality and by the styles of academic engagement and tenacity obtained through a clúster analysis. Although these results are not extrapolable to similar samples, they serve as ante-cedents to the study of the central constructs addressed in this study.